SIMBA: uma ferramenta Web para gerenciamento de montagens de genomas bacterianos - Diego César Batista Mariano (2015)
The evolution of large-scale sequencing platforms has reduced the time taken for the process of DNA fingerprinting at a reduced cost and in less time. However, sequencers still have limitations, such as the maximum size of DNA fragments that are capable of reading. What drives the need to break the DNA into small pieces before sequencing, being necessary after this step, to rearrange the fragments (reads) so that it can represent the original genome. This process is known as genome assembly. The genome assembly is a complex process dependent on the limitations of sequencers, so there is the need to use several computer programs. In recent years, several strategies for genome assembly have been proposed, but there is still no consensus on the best approach. In this context, we propose a pipeline for the assembly of bacterial genomes, which will be managed by a web application with user-friendly interface called SIMBA (Simple Bacterial Manager for Assemblies). To evaluate its performance, we assembled the strains Corynebacterium pseudotuberculosis 1002 (originally sequenced in Sanger and Roche 454 platforms) and Corynebacterium pseudotuberculosis 258 (originally sequenced on SOLiD v3 platform) using five different assembly software: Mira3, Mira4, Minia, Newbler and SPAdes. Both strains were resequenced with simple fragments libraries of approximate size to 200pb in the semiconductor Ion PGM platform. After assembly, was chosen one of them to perform the closing of gaps through two approaches: reference-based and optical mapping. Finally, it was observed that the SIMBA tool allows fast and easy execution of the assembly process and curation of genomes. The download of the tool is available at the website: <http://ufmgsimba. sourceforge.net>.